2018
DOI: 10.3748/wjg.v24.i45.5179
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging and white light endoscopy in the characterization of a polypectomy scar: A single-blind observational study

Abstract: AIMTo assess the incremental benefit of narrow band imaging (NBI) and white light endoscopy (WLE), randomizing the initial technique for the detection of residual neoplasia at the polypectomy scar after an endoscopic piecemeal mucosal resection (EPMR).METHODSWe conducted an observational study in an academic center to assess the incremental benefit of NBI and WLE randomly applied 1:1 (NBI-WLE or WLE-NBI) in the follow-up of a post-EPMR scar by the same endoscopist.RESULTSA total of 112 EPMR scars were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
(25 reference statements)
1
10
1
Order By: Relevance
“…Another prospective multicenter study, which evaluated 255 colorectal scars after a median of 7 months following a colorectal piecemeal EMR, showed a NPV of 100 % (95 %CI 98 % -100 %) and sensitivity of 100 % (95 %CI 93 % -100 %) for NBI with near-focus imaging [216]. However, slightly lower values were observed in a study of 112 scars, which showed that the accuracy of NBI for the detection of residual neoplasia at the resection site was 86.8 %, compared to 81.6 % for WLE and (P = 0.15) [217]. This study has however several limitations, including the single operator, high recurrence rates, and non-blinded pathologist.…”
Section: Follow-up After Endoscopic Resection Of Lesionsmentioning
confidence: 95%
“…Another prospective multicenter study, which evaluated 255 colorectal scars after a median of 7 months following a colorectal piecemeal EMR, showed a NPV of 100 % (95 %CI 98 % -100 %) and sensitivity of 100 % (95 %CI 93 % -100 %) for NBI with near-focus imaging [216]. However, slightly lower values were observed in a study of 112 scars, which showed that the accuracy of NBI for the detection of residual neoplasia at the resection site was 86.8 %, compared to 81.6 % for WLE and (P = 0.15) [217]. This study has however several limitations, including the single operator, high recurrence rates, and non-blinded pathologist.…”
Section: Follow-up After Endoscopic Resection Of Lesionsmentioning
confidence: 95%
“…Narrow-band imaging (NBI) improves the visibility of vascular structures of colon polyps by using optical interference filters to spectrally narrow the bandwidths used in conventional white light, resulting in more visual detail of the superficial mucosal structures and capillaries seen in neoplastic tissue. 67,68 Several early meta-analyses did not show NBI to improve the ADR compared with white-light colonoscopy. [69][70][71] One meta-analysis did not show any benefit of NBI when compared with high-definition white-light colonoscopy but suggested that it may improve the ADR when compared with standard white-light colonoscopy.…”
Section: Technologymentioning
confidence: 99%
“…However, recent studies have provided new evidence on the efficacy of advanced endoscopic imaging in the detection of residual or recurrent lesions in post-EMR scars [9][10][11][12]. A prospective single-center study, which analyzed 183 scars using systematic narrow-band imaging (NBI) after WLE, showed significantly higher sensitivity and negative predictive values (NPVs) for detection of endoscopic residual neoplasia in a combination of WLE plus NBI vs. WLE alone (93.3 % vs. 66.7 % and 98.6 % vs. 93.6 %, respectively) [9].…”
mentioning
confidence: 99%
“…The only randomized crossover trial to be reported included 112 scars and aimed to evaluate the incremental benefit of NBI and WLE by randomizing the initial technique for the assessment of post-EMR scars [11]. This study did not find significant differences between NBI vs. WLE in sensitivity (85.0 % vs. 78.9 %), specificity (77.1 % vs. 84.2 %), or accuracy (82.5 % vs. 80.0 %), and concluded that scar biopsy was still required [11]. Recently, a classification for post-EMR scar evaluation using specific criteria based on advanced imaging was created and validated [12].…”
mentioning
confidence: 99%